Computer-guided alignment III: description of inter-element alignment effect in circular-pupil optical systems. - Lee, H; Dalton, G; Tosh, I; Kim, S (Optical Society of American (OSA), 2008)
We present an analytic description of the inter-element alignment effect of misaligned optical systems with circular pupils. The description shows that decenter and tilt produce lateral displacement of the field and pupil coordinates, whilst a despace directly modifies the aberration coefficients by perturbing paraxial distances and scale factors of the two coordinates. This reveals that a misaligned surface not only changes its aberration characteristics, but also affects those of subsequent surfaces, which is the essence of the inter-element alignment effect. This description, combined with primary aberration theory, was applied to various misaligned systems to approximate their aberrations and alignment sensitivities given by ray-tracing. The results demonstrate the accuracy and robustness of this approach. We also discuss the potential usefulness of the description in estimating the axial separations between surfaces.